Comparison of teneligliptin with sitagliptin as an add on to metformin in patients of type 2 diabetes mellitus: an observational study - Dange, S. V.; Narkar, Nimish S.; Rane, Pratik; Das, Sayan; Madrewar, Vishwadeep; Kothari, Revati (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Teneligliptin is a new dipeptidyl peptidase-4 (DPP-4) inhibitor, available in India. It has been widely prescribed in type 2 diabetes mellitus (T2 DM) due to its low cost. However, there are few studies comparing it with other DPP-4 inhibitors. The objective of this study is to compare the efficacy of teneligliptin with sitagliptin in patients of T2 DM. Methods: Patients of T2 DM, attending the OPD of a hospital during the period of January to August 2017 were scrutinized. Those uncontrolled on metformin monotherapy (1 g/day) were selected and were administered either sitagliptin (100 mg/day) or teneligliptin (20 mg/day) in addition to metformin. Base-line clinical features (age, sex, body-weight, BP, pulse rate etc.) and laboratory parameters (hemogram, fasting blood sugar and postprandial blood sugar, HbA1c, serum creatinine etc.) were recorded initially and at the end of three months. Side effects were assessed with the help of a questionnaire. The data obtained were analyzed by student’s t-test. P<0.05 was considered as statistically significant. Results: 35 and 32 patients received sitagliptin and teneligliptin respectively. After 12 weeks of therapy, FBS, PPBS and HbA1c significantly reduced in both the groups as compared to base-line values. Both drugs were well tolerated. There was no significant difference in the glycemic parameters between the two groups at the end of the study. Conclusions: Teneligliptin significantly improved glycemic control in patients with T2 DM when prescribed as an add on to metformin. It was equally effective when compared to sitagliptin. As teneligliptin is less costly than other gliptins, it may be considered as a good cost-effective option as an add on to patients of T2 DM uncontrolled on metformin monotherapy.